ROLE OF FUNCTIONAL DISORDERS OF THE GIT IN THE FORMATION OF PATHOLOGICAL HABITATS PATIENTS WITH BODY MISCARRIAGE AMID HYPERANDROGENISM - Semeniuk, L.N.; Likhachev, V.K.; Dobrovol'skaya, L.N.; Taranovskaya, A.A. (World of Medicine and Biology, 2015)
Condition of the gastrointestinal tract is very important preserve immune-endocrine balance of the female body. Hroniostress in metabolic disorders in patients with hyperandrogenism leads to overproduction of cortisol, creates conditions for the development of dysbiosis and the syndrome of "Skip" of the intestine. Determination of secretory IgA in cervical mucus and koprofiltres may serve as a marker of dysfunction of the gastrointestinal tract and to determine the phasing pegravidarnoi training.